igv.js: an embeddable JavaScript implementation of the Integrative Genomics Viewer (IGV) - Robinson, James T; Thorvaldsdottir, Helga; Turner, Douglass; Mesirov, Jill P (Bioinformatics (Oxford, England), 2023)
Abstract Summary igv.js is an embeddable JavaScript implementation of the Integrative Genomics Viewer (IGV). It can be easily dropped into any web page with a single line of code and has no external dependencies. The viewer runs completely in the web browser, with no backend server and no data pre-processing required. Availability and implementation The igv.js JavaScript component can be installed from NPM at https://www.npmjs.com/package/igv. The source code is available at https://github.com/igvteam/igv.js under the MIT open-source license. IGV-Web, the end-user application built around igv.js, is available at https://igv.org/app. The source code is available at https://github.com/igvteam/igv-webapp under the MIT open-source license. Supplementary information Supplementary information is available at Bioinformatics online.